2015
DOI: 10.1073/pnas.1424712112
|View full text |Cite
|
Sign up to set email alerts
|

The ribosome can discriminate the chirality of amino acids within its peptidyl-transferase center

Abstract: The cellular translational machinery (TM) synthesizes proteins using exclusively L-or achiral aminoacyl-tRNAs (aa-tRNAs), despite the presence of D-amino acids in nature and their ability to be aminoacylated onto tRNAs by aa-tRNA synthetases. The ubiquity of L-amino acids in proteins has led to the hypothesis that D-amino acids are not substrates for the TM. Supporting this view, protein engineering efforts to incorporate D-amino acids into proteins using the TM have thus far been unsuccessful. Nonetheless, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
136
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(152 citation statements)
references
References 36 publications
11
136
0
Order By: Relevance
“…This structural information led us to hypothesize that the tRNA helical portion might not be required for flexizyme‐mediated acylation with tRNA analogues. To confirm the veracity of this hypothesis, we compared MhRNA and 4bRNA (5′‐GCCA‐3′) as substrates of flexizymes (dFx and eFx; Figure A) because they were most commonly used for tRNA acylation in previously published studies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This structural information led us to hypothesize that the tRNA helical portion might not be required for flexizyme‐mediated acylation with tRNA analogues. To confirm the veracity of this hypothesis, we compared MhRNA and 4bRNA (5′‐GCCA‐3′) as substrates of flexizymes (dFx and eFx; Figure A) because they were most commonly used for tRNA acylation in previously published studies …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, flexizyme tolerance toward amino acids is based on simple recognition of the aromatic groups in the substrates. The flexizyme eFx, optimized for weakly activated l ‐phenylalanine ( l ‐phenylalanine cyanomethyl ester, l ‐Phe‐CME), can catalyze the acylation of tRNA with various aromatic amino acids, including those with different side chains (e.g., l ‐Phe, l ‐Trp, and l ‐Tyr), with the d configuration (e.g., d ‐Phe, d ‐Trp, and d ‐Tyr), and with N‐modified backbones (e.g., N ‐methyl‐Phe, N ‐acyl‐Phe, and N ‐phenyl‐Gly) . Because the recognition elements are present only on the aromatic groups, the CME moiety in an amino acid substrate was further replaced with a p ‐chlorobenzyl thioester (CBT) to transfer the aromatic recognition moiety from the side chain to the leaving group.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hecht and colleagues tested ribosome variants with mutations in the peptidyl-transferase center, and found several ribosome mutants with substantially increased efficiency to incorporate D- amino acids into a reporter protein in vitro [77]. A recent study by Englander et al provided mechanistic insights into discrimination of D- amino acids by the wild-type ribosome [78]. It was shown that D -aa-tRNAs are accepted by the ribosomal A site and used as substrates for peptide formation.…”
Section: Discrimination Of Amino Acids By the Ribosomementioning
confidence: 99%
“…It was shown that D -aa-tRNAs are accepted by the ribosomal A site and used as substrates for peptide formation. However, ribosomes with D -amino acid in the peptidyl-tRNA (P) site are partitioned into translating and arrested subpopulations, therefore impeding further peptide elongation [78]. …”
Section: Discrimination Of Amino Acids By the Ribosomementioning
confidence: 99%